(untitled) (Malay Literature, 2016)
The political setting that occurred during the political reformation era after 1998 in Indonesia has influenced the literary writings in Indonesia. Forbidden issues are outwardly spoken and afresh. This new situation is assimilated by Leila S. Chudori the author of the novel Pulang. This article discusses his tribulations of the political exile group that lives in exiles in Paris due to Suharto’s politic that hound the people that were connected with communism and feminism tendencies as seen in this novel. These two problems may look different, yet in reality are interlinked based on the post-Suharto’s era socio-politic setting. This article tries to find the answer to those problems through historical and feminism approach. Leila S. Chudori is an Indonesian female writer that deeply perceives the tribulations of the political exile group. They became the victim of Suharto’s government policy that hounds those suspected as the supporters of socialism or leftists group not only in the country but outside of Indonesia such as France. As an exile group the question of identity and relationship becomes significant. After 1998, during the post-Suharto era, with the more open socio-political policy, the Indonesians were given freedom to discuss the problems of the exiles and the opportunity is taken by Leila S. Chudori. The result is the novel Pulang, which talk about the tribulations of the exiles, heightened creatively and more daring compared to during the Suharto’s era, which did not give any consideration to even talk about it. Keywords: Indonesian history; political exiles; supporters of feminism